The identification of victims of human trafficking: definition, challenges and States’ obligations - Corthay, Eric (Indonesian Journal of International Law, 2019)
Human trafficking has been an ever-longing international problem, which violates human rights in various forms of crime. There are many root causes which explain the existence and the rapid rise of human trafficking, including the emerging of supply and demand culture. This raised effort against human trafficking in the international community. These effort is focused on the prevention against trafficking, protection of victims, and prosecution of criminals. Human trafficking itself may be defined by activities revolving around it, the means used, and the purpose of the exploitation itself. The main challenge when encountering human trafficking is the ability to identify the forms of human trafficking, which requires reasonable measures of multidimensional support and protection. However, the obligations provided in several established legal instruments, for example Trafficking Protocol, are sometimes ambiguous, and subsequent State practice shows that they have had rather limited results. Therefore, a better approach is necessary in combatting human trafficking. This might include allowing courts to certify as such any victims who are identified during the proceedings, allowing a judicial or administrative determination to be made based on the application of law enforcement, border control or other officials who encounter victims in the course of investigations or prosecutions; and/or allowing a judicial or administrative determination to be made based on the application of the alleged victim personally or some representative, such as a representative of a non-governmental organization.